2022
DOI: 10.1021/acsnano.1c08377
|View full text |Cite
|
Sign up to set email alerts
|

Bionic Dormant Body of Timed Wake-Up for Bacteriotherapy in Vivo

Abstract: The microorganism has become a promising therapeutic tool for many diseases because it is a kind of cell factory that can efficiently synthesize a variety of bioactive substances. However, the metabolic destiny of microorganisms is difficult to predict in vivo. Here, a timing bionic dormant body with programmable destiny is reported, which can predict the metabolic time and location of microorganisms in vivo and can prevent it from being damaged by the complex biological environment in vivo. Taking the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…They can be genetically modified to express therapeutic and functional molecules, allowing in situ drug production and targeted drug delivery 72 . To design living microorganism-based oral drug delivery vehicles, various technologies have been developed, including microbial and cell cultivation 28,73 , biological surface modification 74 , gene editing 75 and microencapsulation 76 . The post-administration fate of living microorganisms differs between strains and doses 77 , and bioluminescence imaging can be applied to study the dynamic changes of microorganism distribution in vivo.…”
Section: Translational Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be genetically modified to express therapeutic and functional molecules, allowing in situ drug production and targeted drug delivery 72 . To design living microorganism-based oral drug delivery vehicles, various technologies have been developed, including microbial and cell cultivation 28,73 , biological surface modification 74 , gene editing 75 and microencapsulation 76 . The post-administration fate of living microorganisms differs between strains and doses 77 , and bioluminescence imaging can be applied to study the dynamic changes of microorganism distribution in vivo.…”
Section: Translational Considerationsmentioning
confidence: 99%
“…Genetic engineering can improve the safety of microorganisms and provide additional functions such as regulation of the GI microbiota 31,72 . Genetically engineered microorganisms can be programmed to colonize, proliferate and release therapeutic products in specific target environments, thus improving drug efficacy and reducing side effects 28 . Owing to their capacity to self-replicate and constantly express bioactive substances, sustained drug release can be achieved with small doses 87 .…”
Section: Translational Considerationsmentioning
confidence: 99%
“…Among several Eudragit polymers, at pH 5.5, Eudragit L100-55 and L30D-55 dissolve, while Eudragit L100 starts to dissolve at a pH of 6.0. 36,135,136 Taking the enteric advantage of Eudragit polymers, our group developed an Eudragit L100-55-based triggerable nanocoating for on-demand bacterial reactivation in the intestine. Eudragit L100-55 coated EcN presented a higher acid tolerance than the uncoated one.…”
Section: Enhanced Tolerance To Environmental Stressmentioning
confidence: 99%
“…The inactivation of EcN can be attributed to the mineralized coating, which limits the substance exchange and physical space required for probiotic colonization. [22,33] A previous study revealed that the preservation stability of cells coated with mineralized shells can be substantially improved. [32] Then, the reactivation of EcN@CaCO 3 was verified by acid treatment.…”
Section: Preparation and Characterization Of Ecn@cacomentioning
confidence: 99%
“…[18][19][20] For instance, synthetic materials coated with probiotics for surface chemical modification have been developed to achieve on-demand gut delivery. [21][22][23] Encapsulation strategies adopt soft materials, such as polysaccharides and proteins, to protect probiotics from harsh environments and enhance bioactivity and colonic delivery efficiency. [24][25][26] However, these advanced methods only provide temporary protection and incomplete resistance to environmental stresses before reaching the colon, resulting in insufficient therapeutic benefits in clinical research.…”
Section: Introductionmentioning
confidence: 99%